Pembuatan Website Promosi Produk UMKM pada Daerah Setiabudi Kota Bandung dengan Menggunakan Framework Codeigniter: Studi Kasus pada UMKM Buket Bunga 'Dikala' - Naldo Hibatullah, Muhammad Rifqi; Abdullah, Fahmi (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Bouquet UMKM is a small business that sells fresh flowers in bouquet form. In today's digital era, marketing through digital media such as websites has become important to increase sales and expand market reach. Therefore, in this study, a website was created as a digital promotion media for Bouquet UMKM along with an explanation of the online ordering system. Additionally, this study also discusses the use of the CodeIgniter framework in creating the promotional website. In conclusion, using a website as a digital promotion media and an online ordering system is crucial in increasing sales and expanding the market reach of Buket UMKM. The use of the CodeIgniter framework as a tool in creating the promotional website can improve efficiency and website development capabilities.